Experience of using artificial nesting platforms for the Steppe Eagle in the south of Kostanay region, Kazakhstan - Alexey Yu. Timoshenko; Alexander V. Putilin; Radik R. Salemgareev; Georgy Yu. Timoshenko; Kanat Batyrkhanuly (Пернатые хищники и их охрана)
Steppe Eagle (Aquila nipalensis) population currently continues to decline in Kazakhstan, the south of the Kostanay region is no exception. The reasons for the decline are of different nature, both abiotic and biotic, and include the following: destruction of nests by land predators (most often Steppe Eagle nests are located on the ground); steppe fires are of great threat, and the fact that some nests are located on trees and bushes does not help, but rather aggravates the situation; destruction of nests by livestock; developing new areas for farms, etc., as a result, Steppe Eagles are forced to leave favorable nesting territories; electrocution on power poles as Steppe Eagles use traverses to build nests. Artificial structures, such as nesting platforms, are widely used to attract raptors.